2007
DOI: 10.1007/s00256-007-0304-8
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided joint space analysis of the metacarpal-phalangeal and proximal-interphalangeal finger joint: normative age-related and gender-specific data

Abstract: Our data presented gender-specific and age-related normative reference values for computer-aided joint space analysis of the JSD-MCP and JSD-PIP that could be used to identify disease-related joint space narrowing, particularly in patients with osteoarthritis and rheumatoid arthritis commonly involving the peripheral small hand joints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 33 publications
2
36
0
1
Order By: Relevance
“…Additionally, a previous study compared the joint space widths between women and men in 869 healthy subjects. The results showed that women had a significantly smaller total JSD-MCP (-11.1%) compared to men 18 . Age-related changes of joint space width.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Additionally, a previous study compared the joint space widths between women and men in 869 healthy subjects. The results showed that women had a significantly smaller total JSD-MCP (-11.1%) compared to men 18 . Age-related changes of joint space width.…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies have evaluated finger joint space widths in healthy Caucasians measured by CAJSA; in detail continuous reductions of JSD-MCP total (-20.1%), JSD-proximal interphalangeal (PIP) total (-21.4%), and JSD-distal interphalangeal (DIP) total (-24.8%) were observed in healthy subjects between the ages of 30 years compared to 79 years [18][19][20] . Additionally, our study described age-related joint space narrowing in patients with RA.…”
Section: Rheumatologymentioning
confidence: 98%
See 1 more Smart Citation
“…In recently published studies, the excellent precision of CAJSA-parameters was veriWed with a range between 0.53 and 1.23% [16,18], indicating that joint space changes were not based on the precision error of the CAD-technique itself. The high precision of CAJSA may partly be explained by the kind of algorithm and the procedure to detect the joint edges of a bone.…”
Section: Reproducibility Of Computer-aided Joint Space Analysismentioning
confidence: 97%
“…New advances in computer-aided diagnosis (CAD) have led to signiWcant improvements in the Weld of radiogeometrical analysis of joint space widths [7], in particular for the Wnger joint space widths in patients with osteoarthritis and rheumatoid arthritis [8][9][10][11][12][13][14][15][16][17]. The computer-aided joint space analysis (CAJSA) is a recently developed CAD-technique for semiautomated measurements of joint space widths at the Wnger articulations [18].…”
Section: Introductionmentioning
confidence: 99%